2016
DOI: 10.1093/jat/bkw105
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Drugs of Abuse in a Single Sample of Human Teeth by a Gas Chromatography–Mass Spectrometry Method

Abstract: The purpose of this study was to develop and validate a gas chromatography-mass spectrometry method to detect drugs of abuse in a single sample of tooth. Pulverized samples of dental materials were subjected to acid hydrolysis to detect opiates, cocaine and their metabolites. The residual dental materials from these analyses were subjected to basic extraction to detect cannabis products (Δ-tetrahydrocannabinol, cannabidiol and cannabinol). The method showed a good linearity between 0.05 and 2 ng/mg for all sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Samples include blood, plasma, urine, hair, oral fluids as well as in breath, sweat, breast milk, teeth, etc. [24][25][26][27]. The most common samples used for illicit heroin testing are blood, urine and oral fluids.…”
Section: Introductionmentioning
confidence: 99%
“…Samples include blood, plasma, urine, hair, oral fluids as well as in breath, sweat, breast milk, teeth, etc. [24][25][26][27]. The most common samples used for illicit heroin testing are blood, urine and oral fluids.…”
Section: Introductionmentioning
confidence: 99%
“…In many cases of forensic analysis of bodies when other skeletal parts cannot be studied (burned, left for long periods in water or exposed to considerable dehydration), only teeth remain in a usable condition. Some studies suggest that many substances accumulate even in the teeth of drug addicts . Few studies have reported the presence and pharmacological stability of drugs in the teeth of exhumed bodies [i.e., 2 years ].…”
Section: Resultsmentioning
confidence: 99%
“…In a second phase, samples of hair and teeth were analyzed in accordance with the validated procedure to identify chronic use of opioids . One hundred milligrams of finely cut hair and 1 g of pulverized teeth were subjected to hydrolysis with a solution of 0.1 M HCl (24 and 48 h at 50°C, respectively) after the addition of the internal standard (nalorphine 50 ng).…”
Section: Methodsmentioning
confidence: 99%
“…Other organic solvents might be applied in this technique, such as acetonitrile [310], but the extractions may not reveal as efficient. Regarding SPE, the reported sorbents include mainly mixed mode and cation exchange ones such as Oasis MCX [300], Chromabond HR-XA [290], Strata X-C [281,297], CleanScreen [285], Isolute HCX [312], and specific THC sorbents, such as, CEREX HPSPE THC [299]. These conventional sample preparation techniques result, overall, in great cannabinoids recoveries, nevertheless, several drawbacks have been pointed in the most recent years, namely, difficulty in automation, its complicated and time-consuming processes, and the large amounts of sample and organic solvents that they usually require [313].…”
Section: Challenges In the Determination Of Secondary Metabolites mentioning
confidence: 99%
“…In this sense, it is common procedure to confirm by chromatographic techniques any positive result given by the immunoassay [331]. The most common use gas chromatography (GC) coupled to mass spectrometry (GC/MS) [272,285,310,311,312] or flame ionization detector (GC/FID) [303] and liquid chromatography (LC) coupled to mass spectrometry (LC/MS) [301,302,332] or ultraviolet detector (LC/UV) [250,302,305,333]. Nevertheless, GC methods are recognized for its difficulty to identify and quantify acidic cannabinoids such as cannabigerolic acid, cannabidiolic acid, and THCA because they are decarboxylated into their neutral forms during analysis [329,334].…”
Section: Challenges In the Determination Of Secondary Metabolites mentioning
confidence: 99%